The Contemporary Affordable Housing - Sana Sati Abbas; Rana Mazin Mahdi (Iraqi Journal of Architecture and Planning, 2017)
Affordable Housing represents one of the main attitudes depended universally at the main time, to meet the developed housing need, which reflected on the development of the concept to what is called now the contemporary affordable housing which must be differentiated from the traditional affordable housing and determine its privacy according to architectural special thesis, and that brings research problem "there is a gap about the role of contemporary affordable housing principles in the development of residential in general and local projects". The research determined the main items reflected to the concept, which are represented by the contemporary affordable housing principles, site planning and the dwelling units. The research hypotheses was that "the site planning consideration and the dwelling unit have a role according to the contemporary affordable housing in international and local housing projects. The paper studied two examples, one of them is the national, and the other is the local, analyzed them according to the theoretical framework and finally submits the conclusions which shows the integration response system that achieves dimensions of housing development from residential units with high quality technological designs with suitable locations and sizes that achieve high density at low rise, connection to infrastructure, proximity to work and transportation.